DESIGNING OF THE FUZZY CONTROLLER AT IDENTICAL BELL-SHAPED MEMBERSHIP FUNCTIONS - Gostev, V. I. (Radio Electronics, Computer Science, Control, 2010)
Analytical expressions for control actions at the input of a fuzzy controller are derived at identical bell-shaped membership functions, fuzzy controller designing problems are discussed and practical design of a fuzzy controller is proposed.